Effect of FYM and Macronutrients on Onion Seed Yield - V.S. Wani , A.D. Kadlag; A.L. Pharande, S.D. Shinde, C.A. Nimbalkar (Journal of the Indian Society of Soil Science, 2017)
An experiment on onion (Baswant 780) was conducted at the Research Farm of STCRC Project, MPKV, Rahuri in equal strips L0, L1 and L2 in created fertility gradient, which were developed by applying different doses of N, P2O5 and K2O fertilizers. Doses of N were 0, 50, 100 and 150 kg ha-1; P2O5 0, 25, 50 and 100; K2O 0, 25, 50 and 100 kg ha-1; and FYM were 0, 10 and 20 t ha-1 for different onion plots. Out of all combinations, 21 treatment combinations of N, P2O5 and K2O were selected and the experiment was conducted in fractional factorial design. In addition to this, three control plots of N, P2O5 and K2O were also taken in each strip. Method of path coefficient analysis was used for decomposition of correlation between yield and nutrients and their direct and indirect percentage contribution. Study revealed that FYM played an important role in releasing the micronutrients from applied nutrients as well as from soil and enhancing the seed yield of onion. Contributions of macronutrients to onion seed yield with and without FYM were estimated using path coefficient analysis. The direct contribution of FYM was highest (40.9%) followed by applied N, P2O5 and K2O. Contribution of soil nutrients were negligible in FYM plot, while it was the highest (FN : 21.3%, SK : 13.9% and SP :7.2%) in no-FYM plot. Study recommends application of fertilizers with FYM as per yield target for enhancing onion seed production, increasing use efficiency of added nutrients, maintaining soil health and avoiding the mining of soil nutrients.